In Silico Identification of Natural Lead Molecules from the Genus of Phyllanthus Against Hepatitis B Virus Reverse Transcriptase - Sarma, Kishore; Borkakoty, Biswajyoti; Parida, Pratap; Jakharia, Aniruddha; Dey, Dipankar; Biswas, Dipankar; Panda, Debashis; K. Modi, Mahendra; K. Mohapatra, Pradyumna; Mahanta, Jagadish (Natural Products Journal, The, 2016)
Background: Hepatitis B virus claims approximately 780000 human lives each year. Inadequate effectiveness and drug resistance has led to the search for more potent antivirals with minimal risk of resistance. Plant extract from Phyllanthus genus have long been used in traditional medicine as effective antiviral and hepatoprotective agents. Objective: The present study aims to find the active principle of Phyllanthus and their mode of action against Hepatitis B Virus Reverse Transcriptase (HBV RT), a potential drug target of HBV infection. Methods: The 3D structure of HBV RT was modeled and its stability was assessed with a 50ns molecular dynamics simulation. Ninety-three phytochemicals were screened from Phyllanthus and used for docking study taking lamivudine as control drug. Results: Comparison of binding energy suggests that, lupeol acetate, a triterpene of P. niruri, P. reticulatus and P. urinaria showed highest binding energy for both native and M204V mutated HBV RT (-7.95 kcal/mol & -6.16 kcal/mol respectively) than the control drug lamivudine (-4.57 kcal/mol & -3.50 kcal/mol respectively). Subsequently, lupeol acetate was screened for in silico ADME/Tox property and result indicates good bioavailability without toxicity and can be treated as a candidate drug molecule. Conclusion: Further clinical testing may lead to the discovery of a novel HBV RT inhibitor.
Keywords: lupeol acetate